Examination of high Q factor multilayer chip inductor applied magnetic flux path control technology - Kazuhiro Shimura; Yasuyuki Kono; Mitsuhide Sato; Yinggang Bu; Tsutomu Mizuno (Energy Reports, 2020)
Inductors used for power supplies can be miniaturized by increasing the frequency. However, as the frequency increases, the loss in the inductor increases, which hinders the improvement of efficiency. This study suggests a flux path control technology as a method for reducing inductor loss. Herein, we investigate high Q value chip inductors with magnetic flux path control technology. By applying magnetic flux path control technology, the Q value was improved by 35% in comparison with conventional multilayer chip inductors.
Keywords: 330; factor; Magnetic flux path control technology; Multilayer chip inductor; Proximity effect; Skin effect